Comparative Analysis of Acoustic Emission Signals from On-Load Tap-Changers for Potential Detecting of Non-Simultaneous Operations - Andrzej CICHOŃ; Sebastian BORUCKI; Michał WŁODARZ (Archives of Acoustics)
The research reported in this paper deals with the potential of detecting non-simultaneous operation in on-load tap-changer (OLTC) using an acoustic emission method. Tests conducted under laboratory conditions were carried out using an OLTC model. Three transducers with different characteristics were used: WD 17 AH, D9241A, and R15α, alongside oscillography as the reference method. The use of two new descriptors in the time domain was proposed. The feasibility of detecting the defect with different piezoelectric transducers was investigated. As a result of the analysis of the results, it was found that each piezoelectric transducer can identify nonsimultaneous operation of the switch. The most significant changes in descriptor values occurred in the time domain, and the most effective transducer turned out to be R15α.